EKSISTENSI PEDAGANG KELONTONG DI JALAN CIPTA KARYA KELURAHAN SILANG MUNGGU KECAMATAN TAMPAN - Putri, Helvana Yolanda; Kadarisman, Yoskar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was carried out on the road to Cipta Karya Sialang Munggu Village Tampan District. The purpose of this study is to find out the availability of products, product prices, product quality, service quality, and convenience provided by grocery traders in creating customer satisfaction and knowing the efforts made by grocery traders in maintaining their existence. In this study the authors used quantitative descriptive methods and the analytical techniques used were frequency distribution tables and cross tabulation analysis. In this study the technique of determining the sample used was total sampling / census and the number of samples was 65 respondents. Data collection uses observation and guided interviews using a questionnaire. The results showed that the availability of products owned by grocery traders was categorized as incomplete (95.4%). The price of products offered by grocery traders to consumers is categorized as less affordable (93.8%). The quality of products owned by grocery traders is categorized as not good (56.9%). The quality of services provided by grocery traders to consumers is not good (93.8%). And the comfort level given by grocery traders to consumers is categorized as poor (95.4%). To determine the efforts made by grocery traders in maintaining their existence, seen by using 3 measurements of social capital theory, namely: trust, networks and norms. The form of trust is to borrow capital from other parties, there are 33 respondents (50.8%), and provide debt to consumers, there are 42 respondents (64.6%). The form of the network is to work together and buy products at distributors, there are 42 respondents (64.6%). And the form of the norm is the influence of the opening hours of grocery stores that there are 37 respondents (56.9%), and serve consumers kindly that there are 43 respondents (66.2%). Keywords: Product Availability, Product Price, Product Quality, Service Quality, and Comfort